(untitled) (Journal of Medical Sciences, 2022)
To study tumour immunity and vaccines, knowledge of tumour antigens and genes that encode them is essential. Cancer vaccines and cancer immunotherapy have been developed as a fourth type of treatment. There are two main categories of cancer vaccines: prophylactic (preventative) or therapeutic (curative). Prophylactic vaccines are given to healthy individuals whereas, therapeutic cancer vaccines are administered to cancer patients as a treatment, and the option of therapeutic vaccines is the personalized vaccines which are specific for tumour type and individual patient. The identification and characterization of tumour antigens that are highly immunogenic in human tumours are the key issue in tumour immunology. The candidate tumour antigen for cancer vaccine should have a potent effect in elicitation a specific humoral B cell and cellular T cell responses. To design cancer vaccines, it is necessary to identify a tumour antigen that can generate helper and cytotoxic T cells response and present tumour epitopes effectively. Several strategies have been developed to improve T cell-mediated immunotherapy and tumour vaccines. The current review highlights the tumour antigens as the main target for cancer vaccines; presentation of tumour antigens to CD4+ T cells, and strategies for cancer vaccines in terms of effectiveness of this treatment and the factors that affect the efficacy. Prophylactic, therapeutic, and personalized cancer vaccines have significant promise, but significant work remains to realize that potential. Therefore, technological advancements and a better understanding of tumour-host immune interactions are recommended to realize the mechanisms of resistance to the anti-tumour immune response.